A New Era of Submillimeter GRB Afterglow Follow-Ups with the Greenland Telescope - Yuji Urata; Kuiyun Huang; Keiichi Asada; Hiroyuki Hirashita; Makoto Inoue; Paul T. P. Ho (Advances in Astronomy)
Planned rapid submillimeter (submm) gamma-ray-bursts (GRBs) follow-up observations conducted using the Greenland Telescope (GLT) are presented. The GLT is a 12-m submm telescope to be located at the top of the Greenland ice sheet, where the high altitude and dry weather porvide excellent conditions for observations at submm wavelengths. With its combination of wavelength window and rapid responding system, the GLT will explore new insights on GRBs. Summarizing the current achievements of submm GRB follow-ups, we identify the following three scientific goals regarding GRBs: (1) systematic detection of bright submm emissions originating from reverse shock (RS) in the early afterglow phase, (2) characterization of forward shock and RS emissions by capturing their peak flux and frequencies and performing continuous monitoring, and (3) detections of GRBs at a high redshift as a result of the explosion of first generation stars through systematic rapid follow-ups. The light curves and spectra calculated by available theoretical models clearly show that the GLT could play a crucial role in these studies.